153k views
3 votes
3x - 2y = 12
2x + 3y = -5​

User Laplas
by
5.5k points

2 Answers

3 votes

Answer:

Point form : (2,-3)

Equation form : x=2, y=-3

Step-by-step explanation: Solve for the first variable in one of the equations, then substitute the result into the other equation.

Hope this helps you out! ☺

User Anatoliy Kmetyuk
by
5.7k points
4 votes

Answer:

Point Form: (2,-3)

Equation Form:

X=2

Y=-3

Explanation: add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.

User Momer
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.